2016
DOI: 10.1371/journal.pntd.0004931
|View full text |Cite
|
Sign up to set email alerts
|

Working with Zika and Usutu Viruses In Vitro

Abstract: Usutu (USUV) and Zika (ZIKV) viruses are emerging arboviruses of significant medical and veterinary importance. These viruses have not been studied as well as other medically important arboviruses such as West Nile (WNV), dengue (DENV), or chikungunya (CHIKV) viruses. As such, information regarding the behavior of ZIKV and USUV viruses in the laboratory is dated. Usutu virus re-emerged in Austria in 2001 and has since spread throughout the European and Asian continents causing significant mortality among birds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…PS has been associated with apoptotic mimicry and host-cell entry in a number of viruses, including other flaviviruses 25 27 , and may therefore have a role in ZIKV binding and entry. Finally, in contrast to other flaviviruses, ZIKV remains infective at a wider range of temperatures 22 and pH values 23 , which have been further characterized in this work.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…PS has been associated with apoptotic mimicry and host-cell entry in a number of viruses, including other flaviviruses 25 27 , and may therefore have a role in ZIKV binding and entry. Finally, in contrast to other flaviviruses, ZIKV remains infective at a wider range of temperatures 22 and pH values 23 , which have been further characterized in this work.…”
Section: Introductionmentioning
confidence: 84%
“…In addition to studying the interactions between these receptors and ZENV, we wished to examine parameters that affect the binding process, such as the presence of crizotinib (Cz) or phosphatidylserine (PS), as well as the effects of temperature 22 and pH 23 . Cz is an ATP mimic that has been shown to interfere with AXL kinase activity 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The data showed that CHIKV can replicate in maternal and fetal placental cells as well as in EBs. Previous work has shown that the ability for CHIKV to infect and replicate in specific cells types is host-specific as has been shown for multiple flaviviruses [37][38][39]. Thus, it is necessary to identify which cells participate in viral pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the ability for CHIKV to infect and replicate in specific cells types is host specific thus, it is necessary to identify which cells participate in viral pathogenesis [23]. This has also been shown for multiple flaviviruses [24,25]. Reports on CHIKV replication efficiency in mammals and cell lines have shown a range of detection depending on the host [26,27].…”
Section: Discussionmentioning
confidence: 99%